Treatment Patterns and Outcomes among Hospitalized Patients with Venous Thromboembolism in the United States: An Analysis of Electronic Health Records Data. Issue 4 (October 2014) - Menzin, Joseph; Preblick, Ronald; Friedman, Mark; Menzin, Jordan; Frean, Molly; Kwong, Winghan Jacqueline
Abstract: Background: With the advent of new treatment options for venous thromboembolism (VTE), it is valuable to gain insights into current clinical practices.Objective: Assess treatment patterns and recurrence among patients hospitalized for VTE.Methods: This retrospective study evaluated patients hospitalized with an incident VTE diagnosis (index) from 2008 to 2012 in a de-identified electronic health record database. Patients were further required to receive anticoagulant treatment and/or a VTE-related procedure for study inclusion. Patients were excluded if they: (1) did not have a medical encounter in the 6 months before index (baseline); (2) had a prior VTE diagnosis or used an anticoagulant during the baseline period; or (3) had a diagnosis of atrial fibrillation/flutter, cardiomyopathy, or a coagulation disorder during baseline or the year after index (follow-up). Hospitalization for recurrent VTE and bleeding were evaluated.Results: A total of 2060 patients were identified (mean age, 60.9 years; 53.0% women), with a mean length of stay of 8.1 days. Of the VTE types, acute DVT was the most common (41.9%), followed by PE (33.3%), and DVT + PE (24.7%). Almost all patients (96.9%) received anticoagulants, of which 94.3% received heparin and 76.5% received warfarin. Although 77.4% of warfarin users were prescribed it at discharge, only (40.2%) had a warfarin prescription within 30 days of discharge. Overall 30 day, 90 day and 1-year VTE recurrence rates were 2.0%, 4.2%, and 7.5%, respectively, and the major bleeding rate was 6.8%.Conclusion: In a real-world population of hospitalized VTE patients, heparin treatment in combination with warfarin was common. However, continuation of warfarin post-discharge was challenging. Initiatives to improve continuation of therapy may be important to reduce VTE recurrence.